2000
DOI: 10.1136/bjo.84.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scleral buckling and encircling procedures on human optic nerve head and retinochoroidal circulation

Abstract: Aims-To study the eVects of segmental scleral buckling and encircling procedures on tissue circulation in the human optic nerve head (ONH) and choroid and retina. Methods-Using the laser speckle method, the normalised blur (NB) value, a quantitative index of tissue blood velocity, was measured every 0.125 seconds and averaged over three pulses in the optic nerve head (NB ONH ) and choroid and retina (NB ch-ret ) in 10 patients with unilateral rhegmatogenous retinal detachment (mean age 52 (SD 17)). NB ONH , NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
(23 reference statements)
1
30
0
3
Order By: Relevance
“…Several pre-and postoperative factors such as the long duration of macular detachment, alterations in retinochoroidal circulation, and ciliary edema have been reported to be associated with poor visual outcomes of the scleral buckling surgery. [26][27][28][29][30] Our results revealed that the mean comaand spherical-like aberrations at 3 postoperative months were 0.385 ± 0.267 and 0.271 ± 0.156, respectively. Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Several pre-and postoperative factors such as the long duration of macular detachment, alterations in retinochoroidal circulation, and ciliary edema have been reported to be associated with poor visual outcomes of the scleral buckling surgery. [26][27][28][29][30] Our results revealed that the mean comaand spherical-like aberrations at 3 postoperative months were 0.385 ± 0.267 and 0.271 ± 0.156, respectively. Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…12 Normal ocular blood flow in RRD has been reported in several studies, 6,7,9 but the main targets for evaluation were the central retinal artery and the ophthalmic artery 6,7 or choroidal vessels. 9 The blood-flow rate in the major superior and inferior temporal retinal arteries, which were in the attached retinas of the patients with RRD, was measured by the laser Doppler technique. 4,15 It was found to be lower than in the fellow eyes 4 or in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The tissue blood flow in the retina or choroid has been noninvasively measured mainly by laser Doppler velocimetry, 4,5 color Doppler ultrasonography, [6][7][8] the laser speckle method, 9 and the pulsatile ocular blood flow technique. 10 However, the evaluation of the retinal blood flow in the macular area by these techniques has been difficult.…”
mentioning
confidence: 99%
“…In addition, attention has been focused on the changes of retinal blood flow in some retinal diseases in the attempt to understand the etiology and severity of the condition and also to evaluate the outcome of surgery [2,17].…”
Section: Discussionmentioning
confidence: 99%